Pengaruh Aliran-Aliran Falsafat Pemidanaan dalam Pembentukan Hukum Pidana Nasional - Syaiful Bakhri (Fakultas Hukum Universitas Islam Indonesia, 2011)
This research discusses the development of criminal sanction philosophy from time to time. This research is a normative research which has juridical philosophic character. The approach applied in this research is conceptual approach, because of its relation with criminal sanction philosophy which could be the basis of criminal law. The research was performed by using literary study. The legal matters is qualitatively analyzed. Using that method, the conclusions obtained are school of criminal law which developed in its era had influenced the Indonesian criminal legal scholar in formulating and connecting the theoretical framework and the criminal sanction philosophy inside the currently discussed reformation of criminal law either legislation or formal criminal law and material criminal law. School and philosophy of criminal law sanction has the role of reflection of Indonesian criminal law reformation.Key words : The schools of criminal law, philosophy of punishment, national criminal law